شاعرية الصورة في الفيلم السينمائي - حيدر خالد فرمان علي (Al-Adab Journal, 2018)
Throughout cinema’s long history that exceeds one hundred years, the cinematic field has witnessed feverish competition, resulted from the intellectual maturity of this art since it appeared as a new invention by Lu-mere Brothers and others from all over the world, who have presented theories formulating trends and directions made up of experiences of innovators that have contributed in transforming cinema from documentation into an innovation instrument through which the director struggles to display, defend and transmit his issue to reach audience completely, free from timeworn traditions, and full of energy and beauty. The aim of this study is to investigate the current of the poetic scene in the cinema film, and how to create it. This study falls into into five chapters. Chapter One presents the problem of how to create poetic scene in the film as well as terminology with their definitions in accordance with research goals and limits. Chapter Two , The Theoretical Framework, includes three sections: Section One is devoted to the concept and orientation of poetic scene, Section Two studies the cine scene and Section Three for the poetic elements in the cine structure. Chapter Three deals with the descriptive analytic procedures, accredited by a committee of experts and specialists at TV and Cine Arts Department. Five indicators have been selected as follows: The narrative construction of events contributes to film poetic scene. Shooting, lighting features contribute to film poetic scene. Employment of decoration and costumes in achieving film poetic scene. Employment of editing effects plays a vital role in film poetic scene. Employment of sound effects of dialogue, music and silence support scene and back up its truthfulness. Then the researcher has determined the sample and its analysis methods in Chapter Four in the purposeful selection of the film Shakespeare as a Lover. Chapter Five gives results, conclusions, recommendations and suggestions. Results Both lighting and color play an important role in constructing a poetic frame by active embodiment of suspense, excitement and expectation elements. Sound backs up the frame through soft dialogue and modified volume to become more credible for the audience. The director’s aesthetic employment of camera movements can beautify the frame. Editing effects can create poetic atmosphere by calm transition between frames. Costumes and decoration can attract audience by colors and composing frames in the screen to achieve film poetic scene. Recommendations Frame dramatic function interacts with various types of cine weave in an integral unit. Sound track, dialog, musical effects and silence can back up the frame in interpreting and clarifying the whole atmosphere. Cine language elements can affect creating poetic frame by color, lighting, movement and tempo.